Present Pro Programme empowers form 3 students of SMK Dato Mahmud Mat, Pekan - Nabila, Abdul Malek; Noor Raha, Mohd Radzuan (Centre for Modern Languages, 2023)
The Centre for Modern Languages (CML) Community Service Unit, stepped up its commitment through the initiation of Present Pro! programme, held on Tuesday, August 22, 2023, from 2.00 p.m. to 5.00 p.m.